Complications of head and neck radiotherapy: a dental perspective - Buchanan, Glynn Dale; Gamieldien, Mohamed Yasin; Tredoux, Sheree; Uys, Andre; Swanepoel, Nicolaas Jacobus (Archive of Oncology, 2019)
For the treatment of head and neck cancers radiotherapy is frequently and successfully performed by medical specialists. However, a number of complications may occur following such therapy. Many of these complications are diagnosed and treated primarily by dental practitioners and specialists. Whilst some are easily managed, others, such as osteoradionecrosis of the jaw, may be very difficult to treat and have a significant impact on a patient’s quality of life. The following report documents a case where several complications occurred following radiotherapy. Comprehensive dental assessment and treatment prior to, during and after radiotherapy may lead to a reduction of complications. Greater cooperation and understanding between the medical and dental professionals is required during radiotherapy of head and neck cancer patients.
Keywords: complications; head and neck; Radiotherapy